Immunoprecipitation middle-up LC–MS for in vivo drug-to-antibody ratio determination for antibody–drug conjugates. (October 2017) - Davis, John A; Kagan, Mark; Read, Jessica; Walles, Markus; Hatsis, Panos
Aim: Drug-to-antibody ratio (DAR) determination is critical for development of antibody–drug conjugates (ADCs). This work presents a middle-up LC–MS approach for DAR analysis using prelabeled capture beads and in-house fabricated slit-plates.Methodology & Results: Cysteine, engineered cysteine and disulfide-linked ADCs, each with two different linker payloads, were immunocaptured and digested to scFc and F(ab′)2 fragments. At this point, disulfide-linked ADCs were analyzed while cysteine and engineered cysteine ADCs were reduced to LC and Fd′ fragments for analysis. Results were precise, accurate and sensitive, allowing DAR to be determined out to 21 days.Conclusion: This work describes a method that is easily implemented, amenable to high-throughput analysis and does not require specialized reagents or equipment.